Islamic law in the LCC : local expansion of subclass BP - Suja', Balqis ([s.n.], 2000)
This document, is an expansion of BP140-BP158, keeping, insofar as possible, the outline of the Library of Congress's original arrangement. Formerly, the Library used the original LCC allocated arrangement and subdivided BP158 alphabetically for law by subject. The practice had shoehorned the comprehensive and extensive collection of Islamic law materials into a short span of class numbers, resulting lacking logical order of the discipline and inadvertant proximity of law by subject matter, including an overwhelmingly crowded section in the shelflist. The expansion was adopted at IIUM in 1993.